The use of financial market variables in forecasting - Stefan Gebauer (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Financial market indicators can provide valuable information for forecasting macroeconomic developments. In response to the global financial crisis of 2007/2008, the role of financial variables for forecasting has been revisited, and new empirical and theoretical forecasting methods able to explicitly incorporate financial market information have been developed. This roundup discusses characteristics of financial variable movements and the relation to business cycles. It furthermore summarizes some of the new theoretical and empirical approaches at hand for forecasting macroeconomic variables with financial market information, and highlights main challenges forecasters willing to consider financial market information in forecasting exercises have to face.
Keywords: 330